Asuhan Keperawatan Pada Tn. W dengan Gangguan Sistem Persarafan : Stroke Non Hemoragic Di Ruang Gladiol Atas Rumah Sakit Umum Daerah Sukoharjo - Wakhidah, Anisa Nur, Fahrun Nur Rosid, S.Kep., Ns., M.Kes (2015)
Background : Stroke is the third cause of death after myocardial infarction and cancer as well as the number one cause of disability worldwide. The impact of stroke is not only felt by the patient, but also by the family and the surrounding community. Research shows that the incidence of stroke continues to rise in many developing countries (including Indonesia). In fact, many clients who come to the hospital in a state that is already much reduced and the stroke is a disease that requires care and treatment long enough. Aim of research :To implement nursing care in patients with non-hemorrhagic stroke that include assessment, intervention, implementation and evaluation of nursing. Methods : The method used is a case study, namely by performing nursing care in patients with non-hemorrhagic stroke ranging from assessment, intervention, implementation and evaluation of nursing. Results : After 3x24-hour nursing care for patients with non-hemorrhagic stroke risk concerns the ineffectiveness of cerebral tissue perfusion, damage to physical mobility and verbal communication barriers partially resolved and interventions should be continued. Conclusion : These three nursing problems resolved partially, thus requiring further treatment and cooperation with other medical team, patients, and families that are indispensable for the success of nursing care.